Kadar Hemoglobin Pada Pasien Diabetes Melitus Tipe 2 Berdasarkan Stadium Nefropati Diabetik Dalam Skrining Kejadian Anemia - Desyani Ariza; Amirah; Andi Maya Kesrianti (STIKES Columbia Asia Medan, 2025)
Diabetes Mellitus often causes disorders in other organs, one of which is kidney disorders, commonly known as Diabetic Nephropathy. Diabetic Nephropathy (DN) is a chronic microvascular complication of Diabetes Mellitus, which is the main cause of end-stage kidney disease. Decreased hemoglobin (Hb) levels, or anemia, are very common clinical manifestations found in patients with this impaired kidney function. Pathophysiologically, the decrease in hemoglobin in DN patients is multifactorial, involving absolute or relative erythropoietin (EPO) deficiency due to damage to renal peritubular interstitial cells. As a result, there is a significant disruption of erythropoiesis, which can disrupt the process of red blood cell maturation in the hematopoiesis process. Monitoring hemoglobin levels is a crucial parameter because anemia in this DN population often appears earlier and is more severe than in non-diabetic chronic kidney disease patients. Therefore, early identification of fluctuations in hemoglobin levels is crucial in clinical management to prevent worsening of the systemic condition of patients with Diabetic Nephropathy. This study aims to review Hemoglobin levels in Type 2 Diabetes Mellitus Patients Based on Diabetic Nephropathy Stage in Anemia Screening. The method in this study used Descriptive Analytical with a sample of 47 respondents who met the inclusion criteria. The sampling and research location were conducted at Dr. Wahidin Sudirohusodo Hospital, Makassar. Hemoglobin measurements were measured using Sysmex Series XN-1000 with the Flowcytometry tool method. The results of the study found normal Hb levels (not anemic) in 25 respondents (53.20%), Mild Anemia in 6 respondents (12.80%), Moderate Anemia in 13 respondents (27.60%) and Severe Anemia in 3 respondents (6.40%). From these data, it is known that not all Diabetic Nephropathy patients in this study experienced Anemia.